Risk factors associated with symptomatic pulmonary embolism in a large cohort of deep vein thrombosis patients - Kucher, Nils; Tapson, Victor F.; Goldhaber, Samuel Z.; for the DVT FREE Steering Committee (Thrombosis and Haemostasis, 2005)
In patients with deep vein thrombosis (DVT), the factors which predispose to concomitant symptomatic pulmonary embolism (PE) have remained uncertain. From a prospective cohort of 5,451 consecutive patients with ultrasound-confirmed DVT, we analyzed 4,211 patients with a known status for presence (n =639) or absence (n = 3572) of symptomatic PE. Age and gender were similar in DVT plus PE (63.7±15.6 years; 49% men) and DVT patients (63.4±17.3 years; 46% men). Body mass index (BMI) was higher in patients with DVT plus PE (median 29.0, range 15.4–67.0 kg/m2) than in patients with DVT (median 26.8, range 9.7–64.4 kg/m2; p < 0.001). Chronic lung disease (17% vs. 12%; p < 0.001), a personal history of PE (11% vs. 6%; p < 0.001), and a family history of DVT or PE (8% vs. 4%; p < 0.001) were more frequent in DVT plus PE patients. Twenty-seven percent of DVT plus PE patients received prophylaxis prior to the thromboembolic event compared with 32% of DVT patients (p=0.002). Proximal DVT (OR 1.84, 95% CI 1.39–2.43), prior PE (OR 1.68, 95% CI 1.20–2.35), obesity (BMI > 30 kg/m2) (OR 1.65, 95% CI 1.33–2.04), chronic lung disease (OR 1.51, 95%CI 1.13–2.01), as well as omission of prophylaxis (OR 1.30, 95%CI 1.04–1.64) emerged as independent predictors of concomitant symptomatic PE.
Keywords: Deep vein thrombosis; pulmonary embolism; venous thromboembolism